EFFICACY OF ROYAL JELLY ON METHOTREXATE-INDUCED SYSTEMIC OXIDATIVE STRESS AND DAMAGE TO SMALL INTESTINE IN RATS - KAYNAR, Leylagül; Aysun CETIN, Aysun; HACIOGLU, Sibel K; ESER, Barış; KOÇYIGIT, İsmail; CANÖZ, Özlem; TASDEMIR, Arzu; KARADAG, Canan; KURNAZ, Fatih; SARAYMEN, Recep; SILICI, Sibel (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The aim of this present study is to investigate the mucositis caused by methotrexate (MTX), as well as whether the application of royal jelly (RJ) has a protective effect on oxidative stress. This present study included six groups each consisted of 12 Wistar rats. Distilled water (po: peroral) was given to the 1st group as placebo for 10 days and MTX (20 mg/kg, intraperitoneal: ip) on the 7th day. The 2nd group received RJ (50mg/kg, po) for 10 days and normal saline (NS) instead of MTX. RJ (50mg/kg) was given to the 3rd group for 10 days and MTX on the 7th day. The 4th group received RJ (100 mg/kg, po) for 10 days and NS was given intraperitoneally. RJ (100mg/kg) was given to the 5th group for 10 days and a single dose of MTX. Distilled water was given to the 6th (control) group for 10 days and intraperitoneal NS on the 7th day. Malondialdehyde (MDA), glutathione peroxidase and superoxide dismutase were analyzed in blood samples on the 11th day. Morphological and histopathological changes were examined in the intestinal tissue samples. Villus length and mucosal thickness, as well as the villus length/crypt ratio, were significantly decreased with MTX administration, and the semi-quantitative histological evaluation (SQHE) score was measured high (p<0.001). In addition, a decrease in the antioxidant parameters and an increase in the MDA levels were identified. The villus length and SQHE were significantly different in the groups receiving RJ (p<0.001) as compared to the MTX group. Although RJ addition had no effect on the decreased mucosal thickness and villus/crypt ratio in MTX groups, it caused an improvement in the antioxidant levels and a remarkable decrease in MDA levels. Adding RJ has a decreasing effect on the MTX-induced intestinal damage and it has a suppressive effect on MTX-induced oxidative stress by means of increasing antioxidant enzyme activity and decreasing lipid peroxidation.